2007
DOI: 10.1021/jp0720993
|View full text |Cite
|
Sign up to set email alerts
|

Using Intrinsic X-ray Absorption Spectral Differences To Identify and Map Peptides and Proteins

Abstract: The intrinsic variation in the near-edge X-ray absorption fine structure (NEXAFS) spectra of peptides and proteins provide an opportunity to identify and map them in various biological environments, without additional labeling. In principle, with sufficiently accurate spectra, peptides (<50 amino acids) or proteins with unusual sequences (e.g., cysteine-or methionine-rich) should be differentiable from other proteins, since the NEXAFS spectrum of each amino acid is distinct. To evaluate the potential for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
96
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(118 citation statements)
references
References 42 publications
21
96
1
Order By: Relevance
“…There have been many studies of proteins and amino acids in solid form using NEXAFS; every naturally occurring individual amino acid has had its core-level spectra characterized at the C, N, and O K edges (25), and a variety of polypeptides and protein spectra have been measured under similar conditions (26)(27)(28). These data have been used to predict (using a building-block approach) the corresponding spectrum of a protein based on its amino acid composition with reasonable success (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many studies of proteins and amino acids in solid form using NEXAFS; every naturally occurring individual amino acid has had its core-level spectra characterized at the C, N, and O K edges (25), and a variety of polypeptides and protein spectra have been measured under similar conditions (26)(27)(28). These data have been used to predict (using a building-block approach) the corresponding spectrum of a protein based on its amino acid composition with reasonable success (28).…”
mentioning
confidence: 99%
“…These data have been used to predict (using a building-block approach) the corresponding spectrum of a protein based on its amino acid composition with reasonable success (28). Based on such studies, it has been suggested that the difference in π Ã -resonances between a model dipeptide and a protein could be due to spectral differences between an α-helix and a planar structure (26,27).…”
mentioning
confidence: 99%
“…Near-Edge X-Ray Absorption Fine Structure Spectroscopy Synchrotron storage rings permit NEXAFS studies at very low levels of organic C, such as in films of humic fractions extracted from highly complex matrices as found in soil (Schäfer et al, 2003Solomon et al, 2005Solomon et al, , 2007a and in environmentally relevant model systems of pure standards designed to serve as simplified analogs of SOM components (Boese, 1996;Boese et al, 1997;Kaznacheyev et al, 2002;Zubavichus et al, 2005;Solomon et al, 2009). For example, C (1s) NEXAFS has been effectively used in the past to study the structural composition of coal (Cody et al, 1995(Cody et al, , 1996, humic substances (Rothe et al, 2000;Scheinost et al, 2001;Schmidt et al, 2000;Solomon et al, 2005Solomon et al, , 2007a, soil colloids (Schäfer et al, 2003;Schmidt et al, 2003;Schumacher et al, 2005), DOM in soil (Schumacher et al, 2006), total soil (Jokic et al, , and biopolymers such as amino acids and peptides (Boese, 1996;Boese et al, 1997;Kaznacheyev et al, 2002;Stewart-Ornstein et al, 2007;Zubavichus et al, 2005), which have led to unique and novel insights about the structural composition of organic moieties, chemical processes occurring in soils, and how these change as a result of land-cover changes. Carbon K-edge investigations of the molecular-level organic C speciation of thin films of humic fractions usually reveal spectra with multiple energy positions of the main 1s-p* transitions in the fine structure region (284-290 eV) ( Fig.…”
Section: Resolving Key Questions In Soil Biogeochemistrymentioning
confidence: 99%
“…Calculated NEXAFS spectra for N-methylacetamide have, to the best of our knowledge, been reported only for the N and O edges 47 and predicted rough similarities. Although a detailed assignment of the spectral structures cannot be performed on the basis of previous investigations of this molecule, studies of similar molecules [3][4][5]7 suggest that the dominant peak in each NEXAFS spectrum is associated with a 1s→π* transition.…”
Section: Nexafs Spectramentioning
confidence: 97%